A biomass energy flow chart for Fiji. (January 2015) - Chandra, Vineet V.; Hemstock, Sarah L.
Abstract: Terrestrial above ground biomass production and utilization was analyzed for Fiji for the years 2003–2012. The total production of biomass was estimated to be 72.67 PJ of which 24% is from food, 44% of agricultural residues, 10% dung and 22% from forestry. Of the 72.67 PJ biomass produced only 11% was used as fuel, 12% as industrial wood and 24% as food. The unutilized biomass resulted into a loss of 38.5 PJ of energy (44 GJ per capita or 2.56 Mt of wood equivalent) which is 53% of the total biomass theoretically produced. Scrutiny of the availability and use of biomass resources is important if biomass energy is to be used on a sustainable basis. Lack of detailed literature in this area in Fiji potentially opens a path for further detailed studies to understand the full contribution of biomass to future sustainable energy supply. Highlights: We prepared the biomass energy flow chart for Fiji focusing on Forestry, Livestock and Crops. We studied recorded the biomass energy production for Fiji for a period of 10 years. Using the energy contents, we converted the mass to energy potential. We also identified the loss of biomass in Fiji which can have a significant impact if utilized.